2022
DOI: 10.3390/ani12202755
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analyses of Response of Local Ghanaian Tanzanian Chicken Ecotypes to a Natural Challenge with Velogenic Newcastle Disease Virus

Abstract: Newcastle disease is a devastating poultry disease that often causes significant economic losses in poultry in the developing countries of Africa, Asia, as well as South and Central America. Velogenic Newcastle disease virus (NDV) outbreaks are associated with high mortalities, which can threaten household livelihoods, especially in the rural areas, and lead to loss of high-quality proteins in the form of meat and eggs, as well as household purchasing power. In this study, we exposed unvaccinated Ghanaian and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, infectious diseases threaten the health of chickens. Previous studies have revealed that the immune responses of different kinds of indigenous chicken breeds after being infected with pathogens such as Newcastle disease virus showed significant differences [16,17]. The diversity of the MHC, which regulates specific immune responses, was confirmed in Chinese indigenous chickens [18].…”
Section: Introductionmentioning
confidence: 95%
“…However, infectious diseases threaten the health of chickens. Previous studies have revealed that the immune responses of different kinds of indigenous chicken breeds after being infected with pathogens such as Newcastle disease virus showed significant differences [16,17]. The diversity of the MHC, which regulates specific immune responses, was confirmed in Chinese indigenous chickens [18].…”
Section: Introductionmentioning
confidence: 95%